Symbolic construction of queer identities in Victorian queer cinema - Sun, Wenxiao; Abdullah, Karmilah; Ong, Sharon Yong Yee (Visualcom Scientific Publications, 2024)
This article analyzes the symbolic construction of queer identities in Sarah Waters' Neo-Victorian Trilogy using content analysis and film semiotics. It explores postmodern narrative techniques and the symbolism of femininity, focusing on themes of desire, identity, and redemption. The highlight of this article is how Waters' works enrich the narrative and challenge traditional representations, offering new perspectives on gender and sexuality in visual culture, and provide a framework for symbolic of queer film, contributed three themes: sex, salvation and desire. Furthermore, the finding also indicates that the shift of queer films to OTT platforms has diversified queer imagery, encouraging more creators to engage in queer film production and fostering a pluralistic understanding and support for the LGBTQ+ community.